2018
DOI: 10.1001/jamafacial.2017.1329
|View full text |Cite
|
Sign up to set email alerts
|

Use of Condensed Nanofat Combined With Fat Grafts to Treat Atrophic Scars

Abstract: In addition to the physical deformity, there is often great psychological burden of facial scars for patients. In this study, we use condensed nanofat combined with fat grafts in a novel technique to improve atrophic facial scars by raising both the surface and the bottom of the affected area.OBJECTIVE To assess whether the use of condensed nanofat combined with fat grafting can be effective in treating atrophic facial scars from both an aesthetic and a functional perspective. DESIGN, SETTING, AND PARTICIPANTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 44 publications
3
58
0
3
Order By: Relevance
“…Skin pieces and cells were fixed and stained according to the standard protocol. [30] Briefly, slides were washed four times with deionized water and then were incubated in ammoniacal silver solution for 12 hours at 25°C. Following thorough washing in deionized water, slides were incubated in hypo solution for 5 minutes.…”
Section: Masson-fontana Ammoniacal Silver Stainingmentioning
confidence: 99%
“…Skin pieces and cells were fixed and stained according to the standard protocol. [30] Briefly, slides were washed four times with deionized water and then were incubated in ammoniacal silver solution for 12 hours at 25°C. Following thorough washing in deionized water, slides were incubated in hypo solution for 5 minutes.…”
Section: Masson-fontana Ammoniacal Silver Stainingmentioning
confidence: 99%
“…There has also been an increased interest in so-called nanofat injections, which involves highly emulsified fat, used to improve skin texture, scars, and other cutaneous issues. 6 The author does not have any clinical experience using nanofat and defers this expertise to his colleagues who perform this procedure. He has observed that after many years doing fat transfer, there is a finer texture to the skin under areas in which fat has been transplanted.…”
mentioning
confidence: 99%
“…Adipose-derived mesenchymal stem cell therapy in the treatment of knee osteoarthritis: a randomized controlled trial [144] 2019 derer der Wundheilung [5,74,[130][131][132], zur Behandlung von Verbrennungen [131,133], zur Verhinderung von unschöner Narbenbildung [134,135] und zur Förderung der Nervenregeneration [136][137][138]…”
Section: Klinische Studie Jahr Zell-ursprungunclassified